APPEARANCE AND REALITY:: THE RECONCILIATION OF DISCREPANT SIGNS OF EMOTION - Lewin, Zaida (2012)
According to Flavell questions involvingappearance-reality (AR) notions tend to provoke some conceptual errorpatterns in children, specially the younger ones. A Phenomenism errorpattern occurs when reality is assimilated to appearances and the childincorrectly reports appearance when asked to report reality. On the otherhand, the notion of schema, used to denote generic structures of worldknowledge that guide information processing, explains the ocurrence of anIntellectual Realism error pattern, and the child incorrectly reports realitywhen asked to report appearance. Recent research suggests that in orderfor the child to correctly infer real and apparent behaviors she must havein mind simultaneously, two apparently incompatible identities and shemust apply both properties to the same object. This hypothesis implies thedevelopment of Dual Coding Abilities (DCA). The present study questionsthe traditional approach of Contextual Cues (CC) with its emphasis onevents leading up to an outcome, as means to achieve a betterunderstanding of intentional disguising or masking of the inner emotionalexperience of TV Game Show looser constestants. The specific designand conceptualization of this study led to the following expectations: Ss inthe Dual Coding Condition (DCC) would manifest superior performance inAR tasks when compared with subjects in the CCC. Furthermore, apredominance of intellectual realism type of error was expected in Ssexposed to the CCC. The sample consisted of 29 second-graders from apublic school. The main results revealed a superior performance in ARtasks for subjects in the DCA condition. A predominance of Phenomenismerror pattern was detected in the CC condition as compared to DCAcondition. The results are interpreted in terms of Flavell's findings ondistinctions between appearance and reality and possible connectionswith metacognitive processes.